Sublime Theology of the Decline of the Soviet Empire. Akat K. Belykh - E. G. Sokolov (Дискурс)
Introduction. Socio-political disciplines are an important component of the Humanities of the Soviet period of Russian history. Scientific communism, introduced as a compulsory subject in all Higher education institutions of the USSR in the last 30 years of the state's existence, was considered as the final expression of all the theoretical propositions of Marxism-Leninism. The article attempts to consider Scientific communism as a speculative speculative construction that, on the one hand, reproduces the terminological, logical, semantic and operational regulations of classical philosophical systems, and on the other hand, is a privileged mechanism of discursive production. As a typical example of how and through what tools the doctrine is legitimized, the texts of the work of A. K. Belykh, who for almost 30 years headed the Department of the theory of scientific communism at the faculty of philosophy of LSU (now SPBU).Methodology and sources. Methodologically, the work is based on a philosophical analysis of texts representative of the epoch (D. de Tracy, grammar of Port Royal, Soviet Russian philosophers who worked in the Marxist-Leninist tradition, monographs by A. K. Belykh), included in the approved canonical corpus of Marxism-Leninism.Results and discussion. Scientific communism, now virtually removed from historical memory, was an interesting example of how social thought evolved during the Soviet period of Russian history. The corpus of socio-political disciplines, which included Marxist-Leninist philosophy (dialectical materialism and historical materialism), political economy, history of the Communist party of the Soviet Union, and scientific communism, was a single complex of speculative doctrine. All these disciplines, positioned as scientific knowledge, can be fully evaluated only in the context of the main trends in the development of social and philosophical knowledge of the New time, set by the Enlightenment era. Symbolic points of reference here can be considered projects of ”universal grammar” (Port Royal) and ”ideology” (Destute de Tracy).Conclusion. Scientific communism is not an accidental, but characteristic of Russian thought, intellectual construct. Collective, i. e. a large number of people are involved in its implementation, which means it can be considered as a well-formed direction of social thought. Among the historical analogs that use the same strategic and tactical Arsenal of means of expression and discursive fixation, it can be compared and likened to the wellknown speculative constructs of a theological nature: high scholasticism.